Mercury Content Analysis in Cosmetics Sold Freelyon Social Media in Gorontalo City - IRWAN , Irwan; RIDHA, Nadirah Rasyid (International Journal of Environmental, Sustainability, and Social Science, 2023)
Cosmetics have become necessary for humans because of their routine and continuous use. Therefore, the research aims to discover mercury content in cosmetics sold freely on social media in Gorontalo City. Besides, the sampling employs total sampling with a complete sample of 10 items. Therefore, this study is descriptive research with an experimental laboratory method. On the other hand, the qualitative analysis using atomic absorption spectrophotometer (SSA) test unveiled that out of the ten samples of whitening cream, there were eight samples containing mercury, namely sample 1, sample 2, sample 3, sample 5, sample 6, sample 8, sample 9, and sample 10. However, it does not exceed the mercury level under the limit requirements set by the National Agency of Drug and Food Control of the Republic of Indonesia. As a recommendation, in choosing cosmetic products, consumers should pay attention to the benefits and adverse effects and the chemical content that can jeopardize their health and use cosmetic ingredients with a POM number.